A Muslim Reading of the Haustafeln of Ephesians 5:21-33 in Dialogue with Quran 4:34: Does the Text Support a Hierarchical Relation between Husbands and Wives? - Lien Iffah Naf’atu Fina (Asosiasi Teolog Indonesia, 2017)
The essay questions whether Ephesians 5:21-33 supports a hierarchical relation between husbands and wives as an ideal and universal principle. To answer the question, as a Muslim, I share my reading of this passage in dialogue with a similar Qur’anic passage, Q. 4:34. I learn that the two texts have undergone similar history since its emergence until today. Through a contextual reading, I view that even though Ephesians 5:21-33, as well as Q. 4:34, adopted the household concept accepted in the area, which was patriarchal, the author instilled a new higher equal relationship between husbands and wives. In short, this text proposes “an intended transformation” or an “imaginative vision.” Offering a new reading of gender-related texts is a shared struggle in both traditions. It is an important endeavor to make the scriptures speak for today’s world as a powerful basis for social transformation.